Operating room architecture is not a risk factor for surgical site infections - Thorsten Jentzsch (Nature Portfolio, 2021)
Abstract Surgical site infection (SSI) may cause a substantial burden for patients and healthcare systems. A potential risk of different architectures of the operating room for SSI is yet unknown and was subject of this study. This observational cohort study was performed in a university hospital and evaluated patients, who underwent a broad spectrum of orthopedic surgeries in 2016 (open-plan operating room architecture) versus (vs) 2017 (closed-plan operating room architecture). Patients, who underwent surgery in the transition time period from the open-plan to the closed-plan operating room architecture and those, who were treated e.g. for osteomyelitis as index procedure were excluded. The primary outcome was revision surgery for early SSI within 30 (superficial) or 90 (deep or organ/space) days of surgery. Age, gender, American society of anesthesiologists (ASA) classification, and the body mass index (BMI) were considered as potential interacting factors in a logistic regression analysis. The incidence of revisions for SSI was 0.6 percent (%) (n = 45) in the 7'740 included surgical cases (mean age of 52 (standard deviation (SD) 19) years; n = 3'835 (50%) females). There was no difference in incidences of revision for SSI in the open- vs closed-plan operating room architecture (0.5% vs 0.7%; adjusted odds ratio (OR) = 1.34 (95% confidence interval (CI) 0.72–2.49, P = 0.35)). Age and gender were not a risk factor for revision for SSI. However, ASA classification and BMI were identified as risk factors for the incidence of revision for SSI (OR = 1.92 (95% CI 1.16- 3.18, P = 0.01) and OR = 1.05 (95% CI 1.00–1.11, P = 0.05)). The overall incidence of revisions for early SSI after a broad spectrum of orthopedic surgeries was relatively low (0.6%) and independent from the operating room architecture. An increase in ASA classification and possibly BMI, however, were identified as independent risk factors for revision for SSI.